2019
DOI: 10.1111/jvs.12748
|View full text |Cite
|
Sign up to set email alerts
|

Functional and phylogenetic consequences of plant invasion for coastal native communities

Abstract: Question: Do invasions by alien plant species with contrasting trait profiles (Arctotheca calendula, Carpobrotus spp., Conyza bonariensis and Opuntia dillenii) change the functional and phylogenetic structure of coastal plant communities? Location: Atlantic coastal habitats in Huelva (Spain). Methods:We identified species diversity and composition in 220 paired (invaded and non-invaded) plots along the coast (440 plots in total). We measured nine functional traits for every native and invader species, namely, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 74 publications
(93 reference statements)
1
20
0
Order By: Relevance
“…P hylo M aker ’ (Qian & Yin, 2016). The distance of the few species that were not found in the PhytoPhylo database were supplanted by the distance of the closest species of the same genus found in the mega‐phylogeny tree (de la Riva et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…P hylo M aker ’ (Qian & Yin, 2016). The distance of the few species that were not found in the PhytoPhylo database were supplanted by the distance of the closest species of the same genus found in the mega‐phylogeny tree (de la Riva et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…invasion on two Mediterranean islands led to a reduction in species richness, functional diversity, and redundancy of the recipient communities. Also de la Riva et al (2019) reported that Carpobrotus spp., together with Arctotheca calendula , had a great impact on the non‐invaded community due to their functional profile, which makes Carpobrotus spp. better competitors in terms of acquisitive traits (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This result agrees with those of other authors. For example, de la Riva et al (2019) worked in the same area and found that this species was the most functionally dissimilar invader. However, it did not cause many differences in the native species’ trait profiles, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations